Penerapan Model Contextual Teaching And Learning (CTL) untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Sumiati Sumiati (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This research is a classroom action research that aims to determine the application of the Contextual Teaching Learning (CTL) learning model in improving students' motivation and learning outcomes in electrolyte and non-electrolyte solution materials . This research is divided into two cycles consisting of planning, action, observation and reflection stages. The research data collection techniques are as follows: initial observations, observations of teacher activities, questionnaires for student motivation and responses. The data analysis technique is qualitative. The results of the study describe an increasing in student motivation and learning outcomes. Teacher activities were carried out well from 83% (good) to 86.7% (very good). Student motivation has increased from 83% to 86% high motivation. Student learning outcomes increased from 69.4% to 89% (completed). The conclusion of this study describes that the application of the Contextual Teaching Learning (CTL) learning model can increase the motivation and learning outcomes of students in class X IPA 5 at SMA N 1 Bantul effectively.